2017
DOI: 10.1002/adfm.201700878
|View full text |Cite
|
Sign up to set email alerts
|

A Band‐Edge Potential Gradient Heterostructure to Enhance Electron Extraction Efficiency of the Electron Transport Layer in High‐Performance Perovskite Solar Cells

Abstract: As the key component in efficient perovskite solar cells, the electron transport layer (ETL) can selectively collect photogenerated charge carriers produced in perovskite absorbers and prevent the recombination of carriers at interfaces, thus ensuring a high power conversion efficiency. Compared with the conventional single‐ or dual‐layered ETLs, a gradient heterojunction (GHJ) strategy is more attractive to facilitate charge separation because the potential gradient created at an appropriately structured hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 37 publications
1
71
0
1
Order By: Relevance
“…Additionally, the dramatically reduced j SC (only ≈9 mA cm −2 , see Table S1, Supporting Information) in comparison to the other device stacks could be due to surface recombination which is caused by unfavorable band‐bending under severe ion accumulation . In case of the TiO x ‐CdS dual layered ETL, the electron backflow can be effectively suppressed, but the advantage of using high mobility CdS cannot be exploited, because the overall electron mobility is limited by the low‐temperature compact‐TiO x layer …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the dramatically reduced j SC (only ≈9 mA cm −2 , see Table S1, Supporting Information) in comparison to the other device stacks could be due to surface recombination which is caused by unfavorable band‐bending under severe ion accumulation . In case of the TiO x ‐CdS dual layered ETL, the electron backflow can be effectively suppressed, but the advantage of using high mobility CdS cannot be exploited, because the overall electron mobility is limited by the low‐temperature compact‐TiO x layer …”
Section: Discussionmentioning
confidence: 99%
“…c) Schematic diagram of the potential GHJ ETL‐based PSCs, d) schematic illustration of the separation and recombination of photogenerated charges in the devices. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Enhancing Performance Of Pscsmentioning
confidence: 99%
“…However, the architecture of heterojunctions in dual‐layered ETLs was planar and the high electron mobility SnO 2 cannot be fully utilized due to the upper compact TiO 2 . Inspired by Wu's work, Hou et al put forward the GHJ whose energy level structure and architecture is shown in Figure c,d, respectively . They deposited SnO 2 and TiO 2 on FTO glass, respectively, followed by the sintering step.…”
Section: Enhancing Performance Of Pscsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Although the PCE of perovskite solar cells soared to a high value of 22.1% close to single crystalline-silicon-based solar cells, [7] the instability of perovskite material still hinders the development of large-area module and further commercialization. [1][2][3][4][5][6] Although the PCE of perovskite solar cells soared to a high value of 22.1% close to single crystalline-silicon-based solar cells, [7] the instability of perovskite material still hinders the development of large-area module and further commercialization.…”
Section: Thin Filmsmentioning
confidence: 99%
“…Among various molecules, thiophene derivatives enable the electron-rich conjugated π system, which consist of four 2p orbital electrons from carbon atoms and two lone electron pairs from sulfur atom. [1][2][3][4][5][6] Although the PCE of perovskite solar cells soared to a high value of 22.1% close to single crystalline-silicon-based solar cells, [7] the instability of perovskite material still hinders the development of large-area module and further commercialization. [28] Moreover, unlike siloxanes and amines, thiophenes can be directly coordinated to the lead atom by the lone pair of electrons offered by the sulfur atom, which may be directly interacted with the valance band of perovskite.…”
mentioning
confidence: 99%